Reorienting the Principle of Sustainable Development in Investing Policy Utilizing Natural Resources and Energy in Indonesia - Wahyu Nugroho (Purnomo Yusgiantoro Center, 2022)
The exploitation of natural resources affects environmental damage and does not comply with environmental licensing. The purpose of this article to find out and understand related to development through investments that can achieve people's welfare, and analyze the reorientation of sustainable development principles in investing by utilizing pro-environment natural resources. This result is reorientation the principle of sustainable development should be done by integrating the activities of the investment policy of natural resources into the economic system and environmental based budget. The conclusions are first, the perspective of the Indonesian government in development through investments isn't directly proportional to the welfare of the people. Current developments tend to the developmental and anthropocentrism paradigms; and secondly, reorientation on the principle of sustainable development since changing the government's perspective on development using an ecocentrism paradigm, and integrating natural resource investment activities into the economic system or environment-based budgets.